Can black coral forests be detected using multibeam echosounder “multi-detect” data? - Feldens, Peter; Held, Philipp; Otero-Ferrer, Francisco; Bramanti, Lorenzo; Espino, Fernando; Schneider von Deimling, Jens (Frontiers in Remote Sensing, 2023)
The black coral Anthipatella wollastoni forms marine animal forests in the mesophotic zone. The spatial extent of black coral forests is not well known in many regions. Due to its protein and chitin skeleton, the coral is difficult to image using acoustic remote sensing techniques compared to corals with carbonate skeletons. Several manufacturers have recently introduced an additional data type to their multibeam echosounders, called “multi-detection,” which provides additional target detections per beam in addition to the primary bottom detection. In this study, we used a Norbit chirp multibeam echosounder in multi-detect mode to acquire up to three targets in each beam in an area of black coral below 45 m depth off the coast of Lanzarote (Canary Islands, Spain). Multi-detect allows features above and below the primary bottom detection to be identified without the need to store and process water-column data. Black coral can be detected by comparing “multi-detection” data with ground truthing by technical divers and underwater cameras. However, the repeatability of the detections is limited and further sensitivity studies are required.